REPRESENTASI TAWAKAL DALAM LIRIK LAGU “33X” KARYA PERUNGGU (KAJIAN SEMIOTIKA FERDINAND DE SAUSSURE) - Fakhri Adi Aminudien; Nizar Hanafi (An-Nahdliyyah: Jurnal Studi Keislaman, 2025)
The rapid development of communication technology has brought fundamental changes in the way spiritual messages and religious values ​​are distributed and received by contemporary society. In this digital landscape, audiovisual media such as songs and music have proven to be one of the most effective and powerful channels in conveying religious teachings and resonance. This research critically focuses on this phenomenon with the main objective of uncovering the profound meaning of tawakal (relief) reflected in the lyrics of the popular song “33x” by Perunggu. This research uses a qualitative method, this study uses Ferdinand De Saussure's semiotic approach. This analytical framework is used to systematically dissect the linguistic structure of the lyrics, distinguishing between the signifier element (the form or sound of the word) and the signified (the concept or meaning referred to) in order to reveal the contained spiritual message. The results of this study show that the lyrics of the song “33x” do not simply contain, but intensely represent the meaning of tawakal. This song is presented through a complex and highly emotional lyrical narrative, depicting a spiritual journey that begins with the awareness of the necessity of complete surrender to God, then repeatedly reminding the listener to always bind themselves in dhikr and remember Him. This study strengthens the position of music as a contemporary da'wah medium that is relevant for the modern generation.